COVID-19 in health-care workers: lessons from SARS and MERS epidemics and perspectives for chemoprophylaxis and vaccines. (2nd October 2020) - Labetoulle, Rémi; Detoc, Maëlle; Gagnaire, Julie; Berthelot, Philippe; Pelissier, Carole; Fontana, Luc; Botelho-Nevers, Elisabeth; Gagneux-Brunon, Amandine
ABSTRACT: Introduction : The world is now facing the COVID-19 pandemic. Experience with SARS-CoV and MERS-CoV, and early reports about SARS-CoV-2 infection suggest that health-care settings and health-care workers (HCWs) are vulnerable in the context of the emergence of a new coronavirus. Areas covered : To highlight the need for prophylactic strategies particularly for HCWs, we identified SARS-CoV, MERS-CoV, and SARS-CoV-2 outbreaks in health-care settings and the incidence of infections in HCWs by a search on MEDLINE and MEDxRIV (for SARS-Cov-2). To identify prophylactic strategies against, we conducted a search on MEDLINE and clinicaltrials.gov about studies involving SARS-CoV, MERS-CoV, and SARS-CoV-2. Expert opinion : HCWs account for a great part of SARS, MERS, and SARS-CoV-2 infections, they may also contribute to the spread of the disease, particularly in health-care settings, and contribute to nosocomial outbreaks. Some preventive strategies were evaluated in previous emerging coronavirus epidemics, particularly in MERS-CoV. For COVID-19 prevention, different chemoprophylaxis with drug repositioning and new agents are under evaluation, and different vaccine candidates entered clinical development, with clinical trials. HCWs are a crucial target population for pre-exposure and post-exposure prophylaxis.